2016
DOI: 10.20944/preprints201610.0071.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Rapid Magnetofluidic Micromixer Using Diluted Ferrofluid

Abstract: Effective and rapid mixing is essential for various chemical and biological assays. The present work describes a simple and low-cost micromixer based on magnetofluidic actuation. The device takes advantage of magnetoconvective secondary flow, a bulk flow induced by an external magnetic field, for mixing. A superparamagnetic stream of diluted ferrofluid and a non-magnetic stream are introduced to a straight microchannel. A permanent magnet placed next to the microchannel induced a non-uniform magnetic field. Th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
(11 reference statements)
0
7
0
Order By: Relevance
“…Active micromixers depend on different external energy sources to disturb the fluids, increase the contact area, or induce the chaotic advection, thus enhancing the mixing effect. Based on the types of external energy sources, the active micromixers can be further categorized as pressure field driven [ 7 , 13 , 14 , 15 , 16 ], electrical field driven [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], sound field driven [ 6 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ], magnetic field driven [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ], and thermal field driven [ 58 ,…”
Section: Active Micromixersmentioning
confidence: 99%
See 1 more Smart Citation
“…Active micromixers depend on different external energy sources to disturb the fluids, increase the contact area, or induce the chaotic advection, thus enhancing the mixing effect. Based on the types of external energy sources, the active micromixers can be further categorized as pressure field driven [ 7 , 13 , 14 , 15 , 16 ], electrical field driven [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], sound field driven [ 6 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ], magnetic field driven [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ], and thermal field driven [ 58 ,…”
Section: Active Micromixersmentioning
confidence: 99%
“…When the micromixer was placed in a uniform magnetic field, it could serve as both a mixer and a pump. Recently, ferrofluid was extensively employed for the studies on magnetic micromixers [ 48 , 49 , 53 , 56 , 57 ]. A ferrofluid-based microfluidic magnetic micromixer developed by Cao et al [ 48 ] using a hybrid magnetic field generated by some micro-magnets and an external AC uniform magnetic field to apply periodic magnetic forces on the ferro-fluid, thus achieving a high mixing efficiency (97%) in 8 s at a distance of 600 μm from the mixing channel inlet.…”
Section: Active Micromixersmentioning
confidence: 99%
“…Passive micromixers have a chaotic structure 29,30 or planar shapes 31,32 and do not need external actuation to enhance the mixing quality. Active mixers employ external sources of energy, including magnetophoretic force, 33,34 electroosmotic force, 35,36 acoustic force, 37,38 thermal power 39,40 and periodic pressure perturbation 41,42 to perturb the flow filed. The FD and FV approaches have been used to discretize the differential governing equations.…”
Section: Micromixersmentioning
confidence: 99%
“…Utilising embedded electromagnets for magnetofluidic actuation, Mao and Koser [ 24 ] demonstrated that the mixing of two streams can be significantly improved. Hejazian and Nguyen [ 25 ] proposed a rapid and efficient micromixer using a permanent magnet and a magnetic fluid. The permanent magnet induces a non-uniform magnetic field, and correspondingly, a secondary flow, that mixes a non-magnetic stream with another stream containing diluted ferrofluid.…”
Section: Continuous Flow Microfluidicsmentioning
confidence: 99%